THE???????? OF TENSOR PRODUCTS İN DOUBLE ORLİCZ SEQUENCE SPACES - Ayhan, Esi (International Journal of Allied Sciences (IJAS), 2022)
Let ???? be a Banach lattice and ????????2 be an double gai Orlicz sequence space associated to an Orlicz function with the Δ2 − condition. In this paper discuss the some general topological properties of tensor products. 2000 Mathematics Subject Classification. 46B42, 46B28.